2023
DOI: 10.1111/jcmm.17696
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria‐associated endoplasmic reticulum membrane: Overview and inextricable link with cancer

Abstract: The mitochondrial‐associated membrane (MAM) is a physical platform that facilitates communication between the endoplasmic reticulum (ER) and mitochondria. It is enriched with many proteins and enzymes and plays an important role in the regulation of several fundamental physiological processes, such as calcium (Ca2+) transfer, lipid synthesis, cellular autophagy and ER stress. Accumulating evidence suggests that oncogenes and suppressor genes are present at the ER‐mitochondrial contact site, and their alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 161 publications
(280 reference statements)
0
7
0
Order By: Relevance
“…Differently from MFN1, a small fraction of MFN2 has been observed to be located in ER membranes juxtaposed to outer mitochondrial membranes. MFN2 deletion is reported to induce an ER stress, through a mechanism still under debate (Yang et al., 2023), which can lead to a deterioration of cellular functions (Filadi et al., 2018).…”
Section: Cell Metabolism Correlates With Mitochondrial Morphodynamicsmentioning
confidence: 99%
“…Differently from MFN1, a small fraction of MFN2 has been observed to be located in ER membranes juxtaposed to outer mitochondrial membranes. MFN2 deletion is reported to induce an ER stress, through a mechanism still under debate (Yang et al., 2023), which can lead to a deterioration of cellular functions (Filadi et al., 2018).…”
Section: Cell Metabolism Correlates With Mitochondrial Morphodynamicsmentioning
confidence: 99%
“…The ER and mitochondria play crucial roles in regulating cellular homeostasis and cell death, especially cross-talk of these organelles mediated by Calcium ion are important for survival of cancer cells [ 34 ]. The link between induction of ROS, activation of the ER stress pathway, and apoptotic death has been demonstrated in various cancer cell lines by various natural compounds [ 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…During ER stress, IRE1 interacts with Sig-1R to promote dimerization. As a calcium receptor, when ER calcium is depleted, Sig-1R dissociates from GRP78, thereby promoting the transfer of calcium to mitochondria through IP3R [ 84 ]. Previous studies have demonstrated that PERK is abundantly present in the ER and MAM in high glucose-cultured cardiomyocytes.…”
Section: Er Stressmentioning
confidence: 99%